WORKSHOP MEMBANGUN KOMPETENSI MAHASISWA UNIVERSITAS 17 AGUSTUS 1945 JAKARTA DALAM MANAJEMEN KEUANGAN, PENGADAAN, DAN FASILITAS PERUSAHAAN - Nabila, Alfina; Pravitasari, Endyastuti (Jurnal Abdimas Bina Bangsa, 2024)
This community service journal is about "Workshop on Building Competencies of Students of Universitas 17 Agustus 1945 Jakarta in Financial Management, Procurement, and Company Facilities". This community service journal is motivated by the need for Practical Competence in the World of Work, Preparation for Competition in the World of Work and Adjustment to Industry Trends. This study aims to determine whether there is an influence on the competence of students of Universitas 17 Agustus 1945 Jakarta in knowledge of Financial Management, Procurement and Facilities. Data processing for this community service journal uses the t test for two related groups where this is to determine whether there is an influence after the implementation of workshop activities by conducting pre and post tests. The result of the t test is that there is an influence on the competence of students of Universitas 17 Agustus 1945 Jakarta in knowledge of Financial Management, Procurement and Facilities